Developing Oral Interaction Skills in Foreign Language Learners through Media Literacy - Neiva Montaño, Heydi Karen (Colombian Applied Linguistics Journal, 2021)
Few studies in Colombia have incorporated media literacy in TEFL (Teaching English as a Foreign Language) environments. This paper presents the results of a research conducted in an upper-intermediate course in the Language Institute of the District University (ILUD) in Bogotá. A media literacy model was adapted to create weekly radio workshops in an eight-week pedagogical intervention. During the research study, data were collected from the participants' weekly interactions, discussions, reflections, as well as from semi-structured interviews and field notes taken from my observations as a participant-observer. It was found that EFL learners from a mixed-ability group were engaged in media literacy practices, mainly when they reflected upon news through their realities, beliefs, and attitudes. The results of this study demonstrated that students developed oral interaction skills and acquired diverse strategies that helped them discuss messages from different media outlets, express their personal opinions, and gather additional information to support their findings.